High concentration of sodium chloride could induce the viable and culturable states of Escherichia coli O157:H7 and Salmonella enterica serovar Enteritidis. (6th March 2021) - Song, Hana; Lee, Sun‐Young
Abstract: In the present study, Escherichia coli O157:H7 and Salmonella enterica serovar Enteritidis were transferred into Luria–Bertani medium without NaCl (LBWS) and adjusted to various pHs (4, 5, 6 and 7) with lactic acid containing 0·75, 5, 10 and 30% NaCl, and stored at 25°C until the bacterial populations reached below detectable levels on tryptic soy agar (TSA). Although E .  coli O157:H7 and S . Enteritidis did not grow on TSA when incubated in LBWS with 30% NaCl for 35 and 7 days, more than 60 and 70% of the bacterial cells were shown to be viable via fluorescent staining with SYTO9 and propidium iodide (PI), respectively, suggesting that a number of cells could be induced into the viable but nonculturable (VBNC) state. These bacteria that were induced into a VBNC state were transferred to a newly prepared tryptic soy broth (TSB) and then incubated at 37°C for several days. After more than 7 days, E .  coli O157:H7 and S . Enteritidis regained their culturability. We, therefore, suggest that E .  coli O157:H7 and S . Enteritidis entered the VBNC state under the adverse condition of higher salt concentrations and were revived when these conditions were reversed. Abstract : Significance and Impact of the Study: Long‐term survived Escherichia coli O157:H7 and Salmonella enterica serovar Enteritidis are major pathogens associated with outbreaks of food‐borne illness. This study highlights two pathogens that could be induced into a viable but nonculturable (VBNC) state under higher salt concentrations and then resuscitated when these conditions are removed. These results would contribute to a better understanding of the VBNC state of E .  coli O157:H7 and S . Enteritidis with changing conditions.